Gambaran Regulasi Emosi Remaja Perempuan Yang Menikah Di Bawah Umur - Amalia, Kingkin Rizki; , Dr. Lisnawati Ruhaena, S.Psi, M.Si, Psi (2017)
Early marriage did by teenagers who have not reached a mature age for marriage. The emotionally of teenager is unstable so they not have the ability to resolve their conflicts and not have a mature mindset about the best future for himself. The girl who commit in early marriage are expected to keep his emotions for stable and can respond the emotional effects with possitive if that arise. It requires a strategy that can be applied to deal with emotional situations that is emotion regulation. These researchers used interview and observation method as a data collection tool. Analysis of the data used in this research is content analysis. Results from this reaseach showed that adoelence who commit in early merriage because of unwed pregnancy are required to all ready facing marriage caused an uneasy and guilty feeling. But for adolescent married with willingly, adolescents feel happier after it. Emotion regulation process includes the situation selection where situations can cause emotions, then change turbulent situation with soothing activity. The next stage, adolescents distract from the situation which makes emotions and adolescents positive thinking, thereby reducing the strong influence of emotions. Response modulation is adolescents arrange their emotions so that not to express in negative emotions. Factors that affect emotion regulation are stressor, cognition, religiosity and support.